Accumulation and distribution dynamics of biomass, phosphorus, and starch in cassava fertilized with or without phosphorus during long growth cycles - Magolbo, Luis Augusto de Souza [UNESP]; Nascimento, Layana Gomes Do [UNESP]; Fernandes, Adalton Mazetti [UNESP]; Guedes, Politon Thiago Pereira [UNESP] (Revista Brasileira de Ciencia do Solo, 2024)
Phosphorus (P) is one of the most important nutrients for plant growth. In cassava, P promotes plant growth and alters the synthesis and accumulation of starch in the storage roots. This study aimed to understand the dynamics of the accumulation and distribution of biomass, P, and starch in cassava plants fertilized with or without P during long growth cycles. A randomized block design with a split-plot scheme and four replicates was used. Plots were represented by the application of 0 (zero) or 70 kg ha-1 P, and the subplots were represented by 12 plant-harvesting times in a 21-month cycle (1, 2, 3, 5, 7, 9, 11, 13, 15, 17, 19, and 21 months). During the first vegetative cycle, P uptake by plants was high; during the second vegetative cycle, P allocation to the roots was greater than P uptake from the soil. Phosphorus supply promoted a late increase of 19-23 % in starch accumulation in cassava plants. Storage roots were stronger sinks for starch than stems during the first vegetative cycle; however, the contribution of stems increased during the second vegetative cycle. Unfertilized plants consumed more storage root starch reserves to maintain shoot regrowth at the beginning of the second vegetative cycle. Supply of P to cassava is a fundamental management practice for increasing starch accumulation in storage roots harvested with long vegetative cycles.
Keywords: carbohydrate remobilization; Manihot esculenta; phosphorus concentration